CircVMA21 ameliorates lipopolysaccharide (LPS)-induced HK-2 cell injury depending on the regulation of miR-7-5p/PPARA - Fu Wang; Fangfang Zhang; Qiangqiang Tian; Kai Sheng (Autoimmunity, 2022)
Accumulating evidence suggests that circular RNAs (circRNAs) are implicated in diverse human diseases, including sepsis-engendered acute kidney injury (AKI). In this study, we investigated the functions of circRNA vacuolar ATPase assembly factor VMA21 (circVMA21) in septic AKI through establishing septic AKI in vitro model. Quantitative real-time polymerase chain reaction (qRT-PCR) assay was adopted to determine the levels of circVMA21, microRNA-7-5p (miR-7-5p) and peroxisome proliferator activated receptor alpha (PPARA) mRNA. Cell Counting Kit-8 (CCK-8) assay and flow cytometry analysis were conducted to evaluate cell viability and apoptosis. Western blot assay was used for protein levels. Enzyme-linked immunosorbent assay (ELISA) was performed for the secretion of inflammatory cytokines. The levels of oxidative stress markers were examined with specific commercial kits. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were utilized the analyse the relationships among circVMA21, miR-7-5p and PPARA. CircVMA21 was reduced in sepsis patients’ serums and LPS-stimulated HK2 cells. CircVMA21 overexpression reversed the suppressive effect on cell viability and the promotional effects on cell apoptosis, inflammation and oxidative stress in HK2 cells mediated by LPS. CircVMA21 was identified as the sponge for miR-7-5p. MiR-7-5p overexpression abrogated the impacts of circVMA21 elevation on cell viability, apoptosis, inflammation and oxidative stress in LPS-stimulated HK2 cells. MiR-7-5p directly targeted PPARA, and miR-7-5p inhibition ameliorated LPS-induced HK2 cell damage by targeting PPARA. CircVMA21 overexpression alleviated LPS-stimulated HK2 cell damage through the regulation of miR-7-5p/PPARA.